Ten Outstanding Young Men (TOYM) 2001 awardees - Go, Josiah (Animo Repository, 2001)
Marketing Professor Josiah Go (BSC-Management '82) was one of the TOYM (Ten Outstanding Young Men 2001) awardees. Her Excellency, President Gloria Macapagal-Arroyo personally handed the award to him, along with nine awardees at Malacanang Palace.